Intention, choice, and the medial frontal cortex. - Rushworth, M (2008)
The medial frontal cortex (MFC) has been identified with voluntary action selection. Recent evidence suggests that there are three principal ways in which the MFC is an essential part of the neural circuit for voluntary action selection. First, the MFC represents the reinforcement values of actions and is concerned with the updating of those action values. Because it is particularly concerned with the rate at which action values should be updated, it mediates the influence that the past reinforcement history has over the next choice that is made and it may determine the learning rate. The MFC's representation of action value does not just reflect the potential reward associations of an action but instead represents both the reward and effort costs that are intrinsic to the action. Second, the MFC is important when an exploratory action is generated in order to obtain more information about action values and the environment. Third, the MFC is critical when conflicting information in the immediate environment instructs more than one possible response. In such situations the MFC exerts an influence over how actions will be chosen by other motor regions of the brain.